Silicon-based / silicon carbide / graphene composite material as well as preparation method and application thereof

By using Joule heating and laser radiation technology in lithium-ion batteries to form a silicon carbide interface, and combining ball milling and freeze-drying processes, silicon-based/silicon carbide/graphene composite materials are used in lithium-ion batteries, solving the problems of volume expansion and particle crushing of silicon-based materials during lithiation, achieving efficient charge transfer and long-life battery performance.

CN119764380APending Publication Date: 2025-04-04ANHUI GLANCO NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411891040.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, silicon-based negative electrode materials will undergo severe volume expansion and particle crushing during the lithiation process, resulting in rapid degradation of battery capacity. The traditional carbon coating is not brittle enough, making it difficult to withstand stress changes during repeated cycles.

Method used

By utilizing the ultra-fast high-temperature characteristics of Joule heating, a silicon carbide interface is formed, three-dimensional porous graphene is prepared in combination with laser irradiation, and the silicon-based particles are uniformly anchored in the graphene frame through ball milling and freeze-drying to form a silicon-based/silicon carbide/graphene composite material.

Benefits of technology

The robust connection between silicon-based materials and graphene is achieved, stress changes caused by volume expansion are alleviated, the rapidity and stability of charge transfer are improved, and the cycle life and rate performance of lithium-ion batteries are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764380A_ABST
    Figure CN119764380A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-based / silicon carbide / graphene composite material and a preparation method and application thereof, and relates to the technical field of lithium ion batteries, the preparation method comprises the following steps: (1) irradiating a carbon-containing substrate with laser to obtain three-dimensional porous graphene; (2) uniformly mixing the graphene prepared in the step (1) with a silicon-based material and a solvent to obtain silicon-based / graphene slurry; (3) drying the silicon-based / graphene slurry prepared in the step (2) to obtain a silicon-based / graphene composite material; and (4) carrying out flash Joule heat on the silicon-based / graphene composite material prepared in the step (3) to obtain the silicon-based / silicon carbide / graphene composite material. The silicon-based / silicon carbide / graphene composite material prepared by the invention can be applied to a lithium ion battery as a negative electrode material, and has relatively high lithium storage capacity and excellent long-term cycle life and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a silicon-based / silicon carbide / graphene composite material and a preparation method and application thereof. Background Art

[0002] The current most advanced graphite anode has a specific capacity of 360-365 mAhg -1 , compared with its theoretical specific capacity (372mAhg -1 ) is very close, but cannot meet the high energy density requirements of the next generation of lithium-ion batteries. Silicon-based negative electrode materials have a high theoretical specific capacity (2000-4200 mAhg -1 ), low working potential (<0.4V), and abundant reserves offer broad prospects for the next generation of high energy density lithium-ion batteries. However, silicon undergoes severe volume expansion and particle crushing during lithiation and separates from the conductive components, resulting in rapid degradation of battery capacity.

[0003] To overcome the above challenges, the internal stress generated during lithiation can be relieved by reducing the size of the active material to the nanoscale. Another strategy to improve the lithium storage performance of silicon-based anodes is to encapsulate silicon-based nanoparticles in a carbon matrix to relieve the stress caused by expansion and prevent direct contact with the electrolyte, thereby improving the conductivity of the material. Generally, the preparation of carbon coatings on silicon-based materials involves the use of organic carbon precursors for coating and subsequent high-temperature carbonization. However, these carbon coatings are often brittle and tend to break during the repeated expansion of silicon-based materials. In order to solve these obstacles, it is necessary to rationally design the structures of silicon-based materials and carbon matrices, such as hollow, core-shell, and porous structures. Although some satisfactory results have been achieved, the high cost and cumbersome manufacturing process limit its large-scale production. In addition to this bottom-up approach, silicon-based particles can also be embedded and encapsulated into already stable carbon structures, such as graphene, carbon nanotubes, etc. However, the traditional method of mixing silicon-based particles with carbon matrices relies on physical mixing. Due to the uncontrollable aggregation of silicon-based particles, this method often makes it difficult to achieve the uniformity of each component in the composite material. In addition, silicon-based materials and carbon components often rely only on physical connections or weak bonds, which are difficult to resist the gaps caused by the volume expansion and contraction of silicon-based materials during repeated cycles, resulting in easy loss of electrical contact with conductive components during charge and discharge cycles, causing rapid deterioration of cycle life and hindering their application in commercial batteries. Therefore, there is an urgent need to develop an efficient and scalable method that can achieve effective encapsulation of silicon-based materials by carbon matrices and maintain a robust interface connection between the two. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a silicon-based / silicon carbide / graphene composite material, and to apply the prepared silicon-based / silicon carbide / graphene composite material as a negative electrode material to a lithium-ion battery, which has a high lithium storage capacity and excellent long-term cycle life and rate performance.

[0005] The present invention overcomes the phase separation problem between silicon-based materials and graphene substrates in the traditional heat treatment process by utilizing the ultra-fast high-temperature characteristics of Joule heating, and forms silicon carbide at the interface between silicon and graphene, thereby firmly connecting silicon and graphene. Despite repeated volume fluctuations during the charge and discharge cycle, the silicon-based material can be stably anchored in the graphene, maintaining stable and rapid charge transfer. In addition, the effective encapsulation of the graphene layer can also resist the adverse reaction of repeatedly exposed fresh silicon-based materials with the electrolyte.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] One of the purposes of the present invention is to provide a method for preparing a silicon-based / silicon carbide / graphene composite material, the preparation method comprising the following steps:

[0008] (1) Using laser to irradiate a carbon-containing substrate to obtain three-dimensional porous graphene;

[0009] (2) uniformly mixing the graphene prepared in step (1) with a silicon-based material and a solvent to obtain a silicon-based / graphene slurry;

[0010] (3) drying the silicon-based / graphene slurry prepared in step (2) to obtain a silicon-based / graphene composite material;

[0011] (4) subjecting the silicon-based / graphene composite material prepared in step (3) to flash Joule heat to obtain a silicon-based / silicon carbide / graphene composite material.

[0012] A second object of the present invention is to provide a silicon-based / silicon carbide / graphene composite material prepared by the aforementioned preparation method.

[0013] The third object of the present invention is to provide the use of the silicon-based / silicon carbide / graphene composite material as a negative electrode of a lithium-ion battery.

[0014] The beneficial effects of the present invention are:

[0015] 1. The present invention uses laser radiation technology to obtain three-dimensional graphene on a polymer substrate. The three-dimensional structure of graphene can effectively encapsulate and physically confine silicon-based materials, prevent particles from falling off, and alleviate stress changes during the volume expansion of silicon-based materials. The three-dimensional hierarchical porous structure can significantly reduce the spatial span of ion transport and reduce ion diffusion resistance. The three-dimensional graphene increases the contact area with the silicon-based material, which is conducive to forming a continuous and stable conductive network and alleviates the self-agglomeration tendency of silicon-based particles.

[0016] 2. The ball milling process of the present invention can fully break up the graphene and silicon-based particle agglomerates and enable the silicon-based particles to be evenly anchored in the graphene framework. The freeze-drying process can ensure that the silicon-based / graphene composite material is minimally disturbed during the solvent removal process to prevent the structure from being destroyed.

[0017] 3. The flash Joule heat treatment of the present invention can quickly heat up in a very short time, thereby providing the shortest reaction time for the migration of silicon-based particles in the graphene matrix during the electrothermal treatment process, and quickly welds the silicon-based particles and graphene together to form a silicon carbide interface phase, firmly anchoring the silicon-based particles in the graphene matrix, and even if repeated volume changes occur during the charge and discharge cycle, fast and stable charge transfer can be achieved.

[0018] 4. The silicon-based / silicon carbide / graphene composite material prepared by the present invention can be applied to negative electrode materials of lithium-ion batteries, and has excellent cycle capacity and long life as well as satisfactory rate performance. The synthesis method is fast, highly controllable, and has good scalability, which may promote the commercial application of silicon-based negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a scanning electron microscope image of the elemental silicon particles in Example 1;

[0020] Figure 2 is a scanning electron microscope image of the laser-induced graphene prepared in Example 1;

[0021] Figure 3 is a transmission electron microscopy image of the silicon / silicon carbide / graphene composite material prepared in Example 1;

[0022] Figure 4 is a transmission electron microscope image of the silicon / graphene composite material prepared in Comparative Example 1;

[0023] Figure 5 The cyclic voltammetry curve of a lithium ion half-cell using the silicon / silicon carbide / graphene composite material prepared in Example 1 or the silicon / graphene composite material prepared in Comparative Example 1 as the negative electrode material;

[0024] Figure 6The cycle performance curve of a lithium ion half-cell using the silicon / silicon carbide / graphene composite material prepared in Example 1 or the silicon / graphene composite material prepared in Comparative Example 1 as the negative electrode material;

[0025] Figure 7 The electrode using the silicon / silicon carbide / graphene composite material prepared in Example 1 or the silicon / graphene composite material prepared in Comparative Example 1 as the negative electrode material is heated to 0.1 Ag. -1 Surface morphology after 100 cycles at the same current density. DETAILED DESCRIPTION

[0026] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0027] The present invention provides a method for preparing a silicon-based / silicon carbide / graphene composite material, the preparation method comprising the following steps:

[0028] (1) Using laser to irradiate a carbon-containing substrate to obtain three-dimensional porous graphene;

[0029] (2) uniformly mixing the graphene prepared in step (1) with a silicon-based material and a solvent to obtain a silicon-based / graphene slurry;

[0030] (3) drying the silicon-based / graphene slurry prepared in step (2) to obtain a silicon-based / graphene composite material;

[0031] (4) subjecting the silicon-based / graphene composite material prepared in step (3) to flash Joule heat to obtain a silicon-based / silicon carbide / graphene composite material.

[0032] In the present invention, the laser is one or more of solid laser, liquid laser, gas laser, semiconductor laser, pulse laser and continuous wave laser.

[0033] In the present invention, the laser wavelength of the laser irradiation is 0.1-50 μm, the laser power is 0.1-1000 W, the scanning rate is 0.1-2000 mm / s, the scanning spacing is 0.01-100 mm, the pulse frequency is 0.001-1000 kHz, the focal length is 0.1-200 cm, and the pressure range of the scanning irradiation is 0.01-1000 kV.

[0034] In the present invention, the carbon-containing substrate is at least one of a synthetic polymer and a natural polymer. Further, the synthetic polymer includes but is not limited to at least one of a carbon chain polymer, polyethylene, polystyrene, polysulfide rubber, polyvinyl chloride, polystyrene, polycarbonate, polyethylene terephthalate, polyetheretherketone, polyether, polyimide, polyester, polyamide, and polyurethane. Further, the natural polymer includes but is not limited to at least one of lignin, cellulose, chitosan, starch, polysaccharide, chitin, and derivatives thereof.

[0035] In the present invention, the carbon-containing substrate may be in the form of at least one of a solid film, a solid powder, a solid fiber, a solid paper, a solid cloth, a solid foam, and a liquid.

[0036] In the present invention, the silicon-based material includes but is not limited to at least one of elemental silicon, silicon monoxide, silicon dioxide, silicon-carbon alloy, and silicon-oxygen-carbon.

[0037] In the present invention, the size of the silicon-based material is 1 nm to 1000 μm.

[0038] In the present invention, the mass ratio of the silicon-based material to graphene is 1:(0.01-500).

[0039] In the present invention, the solvent includes but is not limited to at least one of deionized water, anhydrous ethanol and n-hexane.

[0040] In the present invention, the slurry is mixed by ball milling, the ball milling atmosphere is at least one of air, nitrogen, argon, carbon dioxide, carbon monoxide, hydrogen, and methane, the diameter of the grinding balls for ball milling is 0.1 to 100 cm, the mass ratio of the grinding balls to the silicon-based material / graphene slurry is 1:(0.001 to 1000), the ball milling time is 0.01 to 100 h, the ball milling speed is 10 to 10000 rpm, and the solid content of the slurry is 0.1 to 90%.

[0041] In the present invention, the drying is freeze drying, the freezing temperature is -200 to -5°C, the freezing time is 0.1 to 300 hours, the drying temperature is -100 to 200°C, the drying time is 0.5 to 200 hours, and the vacuum degree is 0.01 to 10 5 Pa, drying times are 1 to 20 times.

[0042] In the present invention, the flash Joule heat temperature is 100-4000K, the voltage is 0.001-10kV, the current is 0.1-100A, the heating rate is 10-3000K / s, the holding time is 0.01-5000s, the cooling rate is 10-2000K / s, and the vacuum degree is 0.001-10 5Pa, the atmosphere is at least one of air, argon, nitrogen, oxygen, hydrogen, and carbon dioxide.

[0043] The present invention provides a silicon-based / silicon carbide / graphene composite material prepared by the aforementioned preparation method.

[0044] In the present invention, the loading amount of the silicon-based material in the silicon-based / silicon carbide / graphene composite material is 0.1-95%.

[0045] The present invention provides use of the silicon-based / silicon carbide / graphene composite material as a negative electrode of a lithium-ion battery.

[0046] The technical solution of the present invention is described in detail below through specific embodiments:

[0047] Example 1

[0048] (1) A polyimide film was irradiated with a carbon dioxide laser with a laser wavelength of 1064 nm, a laser power of 5.5 W, a scanning rate of 100 mm / s, a scanning interval of 0.1 mm, a pulse frequency of 20 kHz, a focal length of 20 cm, and a scanning voltage of 0.1 kV to obtain three-dimensional porous graphene on the surface of the polyimide film.

[0049] (2) Add 100 mg of graphene powder and 200 mg of elemental silicon particles (diameter 200 nm) prepared in step (1) into a ball mill, and add 50 g of deionized water and 60 g of zirconium dioxide spheres (diameter 3 mm), and ball mill for 10 h under argon atmosphere at a ball mill speed of 500 rpm to obtain a uniform silicon / graphene slurry.

[0050] (3) Freezing the silicon / graphene slurry prepared in step (2) in a cold trap for 24 h at a freezing temperature of -50°C. Subsequently, vacuum drying was performed at 25°C for 20 h at a drying vacuum degree of 0.01 Pa. The freeze-drying process was repeated twice to obtain a silicon / graphene composite material.

[0051] (4) placing the silicon / graphene composite material prepared in step (3) in a flash Joule heating device, with a voltage of 50 V, a current of 5 A, a heating rate of 1000 K / s, a holding time of 100 s, a cooling rate of 800 K / s, a vacuum degree of 0.01 Pa, and an air atmosphere, to obtain a silicon / silicon carbide / graphene composite material (Si / SiC / G), wherein the loading amount of elemental silicon is 55%.

[0052] from Figure 1 It can be seen that the size of the elemental silicon particles is about 50nm, spherical and has a smooth surface.

[0053] from Figure 2It can be seen that the three-dimensional graphene prepared by laser irradiation presents a porous structure. The three-dimensional graphene framework can better encapsulate and physically confine silicon particles and increase the contact area with silicon. At the same time, the hierarchical porous structure can reduce the spatial span of ion diffusion and promote rapid ion transport.

[0054] from Figure 3 It can be seen that the silicon / silicon carbide / graphene composite material after Joule thermal flash evaporation shows complete integration, and the silicon particles are completely encapsulated by the graphene layer and dispersed evenly.

[0055] Comparative Example 1

[0056] The preparation method of this comparative example is the same as that of Example 1, except that no Joule heat flash evaporation is performed, that is, the silicon / graphene slurry prepared in step (2) is freeze-dried to directly obtain the silicon / graphene composite material (Si / G).

[0057] from Figure 4 It can be seen that the integrity of the silicon / graphene composite material is not very good, the silicon particles are relatively dispersed, and are not well wrapped by the graphene layer.

[0058] Example 2

[0059] (1) A polystyrene film is irradiated with a carbon dioxide laser with a laser wavelength of 10.6 μm, a laser power of 10.0 W, a scanning rate of 200 mm / s, a scanning interval of 0.2 mm, a pulse frequency of 30 kHz, a focal length of 25 cm, and a scanning voltage of 0.5 kV to obtain three-dimensional porous graphene on the surface of the polystyrene film.

[0060] (2) Add 500 mg of graphene powder and 500 mg of silicon dioxide particles (diameter 100 nm) prepared in step (1) into a ball mill, and add 80 g of deionized water and 50 g of zirconium dioxide spheres (diameter 5 mm), and ball mill for 15 h under argon atmosphere at a ball mill speed of 800 rpm to obtain a uniform silicon dioxide / graphene slurry.

[0061] (3) Freezing the silicon dioxide / graphene slurry prepared in step (2) in a cold trap for 12 h at a freezing temperature of -65°C, and then vacuum drying it at 15°C for 24 h at a drying vacuum degree of 0.02 Pa. The freeze-drying process was repeated once to obtain a silicon dioxide / graphene composite material.

[0062] (4) placing the silicon oxide / graphene composite material prepared in step (3) in a flash Joule heating device, with a voltage of 100 V, a current of 10 A, a heating rate of 1200 K / s, a holding time of 120 s, a cooling rate of 1000 K / s, a vacuum degree of 0.02 Pa, and an argon atmosphere, to obtain a silicon oxide / silicon carbide / graphene composite material, wherein the loading amount of silicon oxide is 65%.

[0063] Example 3

[0064] (1) A polyetheretherketone film was irradiated with a visible light laser with a laser wavelength of 405 nm, a laser power of 12 W, a scanning rate of 350 mm / s, a scanning interval of 0.05 mm, a pulse frequency of 40 kHz, a focal length of 40 cm, and a scanning voltage of 0.5 kV to obtain three-dimensional porous graphene on the surface of the polyetheretherketone film.

[0065] (2) Add 1000 mg of graphene powder and 250 mg of silicon-carbon alloy particles (with a diameter of 1 μm) prepared in step (1) into a ball mill, and add 100 g of deionized water and 80 g of zirconium dioxide spheres (with a diameter of 2 mm). Ball mill for 15 h under an argon atmosphere at a ball mill speed of 1200 rpm to obtain a uniform silicon-carbon alloy / graphene slurry.

[0066] (3) Freezing the silicon-carbon alloy / graphene slurry prepared in step (2) in a cold trap for 48 h at a freezing temperature of -70°C, and then vacuum drying it at 15°C for 40 h at a drying vacuum degree of 0.002 Pa. The freeze-drying process was repeated 3 times to obtain a silicon-carbon alloy / graphene composite material.

[0067] (4) placing the silicon-carbon alloy / graphene composite material prepared in step (3) in a flash Joule heating device, setting the voltage to 120 V, the current to 20 A, the heating rate to 1500 K / s, the holding time to 200 s, the cooling rate to 1200 K / s, the vacuum degree to 0.001 Pa, and the atmosphere to air, and finally obtaining a silicon-carbon alloy / silicon carbide / graphene composite material, wherein the silicon loading is 20%.

[0068] Example 4

[0069] The preparation method of this embodiment is the same as that of Embodiment 1, and the only difference from Embodiment 1 is that the polymer precursor used is polyimide powder.

[0070] Example 5

[0071] The preparation method of this embodiment is the same as that of Embodiment 2, and the only difference from Embodiment 2 is that the diameter of silicon monoxide is 500 nm.

[0072] Example 6

[0073] The preparation method of this embodiment is the same as that of embodiment 3, and the only difference from embodiment 3 is that the flash evaporation atmosphere is nitrogen.

[0074] The silicon / silicon carbide / graphene composite material prepared in Example 1 and the silicon / graphene composite material prepared in Comparative Example 1 were used as negative electrode materials to assemble CR2032 button batteries, and their electrochemical properties were tested. The results are as follows: Figure 5 , Figure 6 , Figure 7 shown.

[0075] The production process of CR2032 button battery is as follows:

[0076] The silicon / silicon carbide / graphene composite, acetylene black and polyvinylidene fluoride were dispersed in N-methylpyrrolidone in a weight ratio of 8:1:1, stirred to form a uniform slurry, and then the slurry was evenly coated on a copper foil with a four-sided coater, with a coating thickness of 12μm, vacuum dried at 60℃, and naturally cooled to room temperature. After punching out a disc with a diameter of 12mm as the working electrode, a lithium metal sheet was used as the counter electrode, and a Celgard2500 membrane was used as a diaphragm to assemble a CR2032 button cell. The electrolyte consisted of 1M LiPF6 dissolved in ethylene carbonate / diethyl carbonate (volume ratio of 1:1). The battery assembly was carried out in an argon-filled glove box to ensure that the oxygen and water content was less than 0.1ppm. The silicon / graphene composite was also assembled into a CR2032 button cell in the same manner as described above. Cycling and rate tests were performed on a LAND-CT2001A battery tester with a voltage range of 0.01 to 3.0 V (relative to Li / Li + The cyclic voltammetry curves were carried out on an electrochemical workstation (CHI660e) with a potential window of 0.01–3.0 V and a scan rate of 0.2 mV s -1 The frequency range of electrochemical impedance spectroscopy is 0.01Hz-100kHz.

[0077] Figure 5The cyclic voltammetry curves illustrate the activation process of Si / SiC / G and Si / G electrodes in the first three cycles. For the Si / SiC / G electrode, an insignificant reduction peak appeared at about 0.5-0.9V in the initial cathodic scan, corresponding to the decomposition of the electrolyte and the formation of the SEI layer. Its reduction peak disappeared in the following cycles, indicating that the SEI layer was formed and stabilized in the first cycle, which hindered the further growth of the SEI and maintained the stability of the electrode-electrolyte interface. In contrast, the reduction peak of the Si / G electrode corresponding to 0.3-1.0V, which is related to the formation of the SEI film, is prominent, indicating that the growth of the SEI occurs at different interfaces and the electrolyte erosion is more serious. This shows that the flash Joule heating process can achieve a better connection between the silicon and graphene interfaces, and the silicon can be effectively coated by the graphene layer during the cycle, alleviating the exposure of the fresh surface caused by volume fluctuations and maintaining the stability of the interface.

[0078] Figure 6 The long cycle performance of Si / SiC / G and Si / G electrodes is shown. All test cells were activated at a low current density of 0.05C in the first three cycles and then tested at a current density of 0.5C. Si / SiC / G showed a higher initial capacity of 1555.0mAhg at a current density of 0.5C. -1 , showing superior capacity retention compared to Si / G. It is worth noting that after 500 cycles, the capacity of Si / SiC / G remained at 1380.0 mAh g -1 , the corresponding capacity retention rate is 89.0%. However, the capacity of Si / G electrode decays rapidly at high current density, and the capacity is only 520mAhg after 500 cycles. -1 .

[0079] Figure 7 The scanning electron microscope images show the characterization of the electrode morphology after cycling. It can be seen that after cycling, huge cracks are generated and expanded on the surface of the Si / G electrode, and the crack depth is large. This structure indicates that the Si / G electrode has undergone severe volume expansion and electrode sheet cracking during repeated cycles, and the particles have fallen off the electrode sheets and lost electrical contact with the conductive components, seriously affecting the cycle life of the electrode. In contrast, the Si / SiC / G electrode maintains its structural integrity, and the cracks are significantly reduced after cycling, indicating that the graphene coating layer cooperates with the silicon carbide interface to be very effective in mitigating volume fluctuations and particle shedding.

[0080] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a silicon-based / silicon carbide / graphene composite material, characterized in that: The preparation method comprises the following steps: (1) Using laser to irradiate a carbon-containing substrate to obtain three-dimensional porous graphene; (2) uniformly mixing the graphene prepared in step (1) with a silicon-based material and a solvent to obtain a silicon-based / graphene slurry; (3) drying the silicon-based / graphene slurry prepared in step (2) to obtain a silicon-based / graphene composite material; (4) subjecting the silicon-based / graphene composite material prepared in step (3) to flash Joule heat to obtain a silicon-based / silicon carbide / graphene composite material.

2. The preparation method according to claim 1, characterized in that: The laser is one or more of solid laser, liquid laser, gas laser, semiconductor laser, pulse laser and continuous wave laser; Preferably, the laser wavelength of the laser irradiation is 0.1-50 μm, the laser power is 0.1-1000 W, the scanning rate is 0.1-2000 mm / s, the scanning spacing is 0.01-100 mm, the pulse frequency is 0.001-1000 kHz, the focal length is 0.1-200 cm, and the pressure range of the scanning irradiation is 0.01-1000 kV.

3. The preparation method according to claim 1, characterized in that: The carbon-containing substrate is at least one of a synthetic polymer and a natural polymer; Preferably, the synthetic polymer is at least one of carbon chain polymer, polyethylene, polystyrene, polysulfide rubber, polyvinyl chloride, polystyrene, polycarbonate, polyethylene terephthalate, polyetheretherketone, polyether, polyimide, polyester, polyamide, and polyurethane; Preferably, the natural polymer is at least one of lignin, cellulose, chitosan, starch, polysaccharide, chitin and derivatives thereof; Preferably, the carbon-containing substrate is in the form of at least one of a solid film, a solid powder, a solid fiber, a solid paper, a solid cloth, a solid foam, and a liquid.

4. The preparation method according to claim 1, characterized in that: The silicon-based material is at least one of elemental silicon, silicon monoxide, silicon dioxide, silicon-carbon alloy, and silicon-oxygen-carbon; Preferably, the size of the silicon-based material is 1 nm to 1000 μm; Preferably, the mass ratio of the silicon-based material to graphene is 1:(0.01-500).

5. The preparation method according to claim 1, characterized in that: The solvent is at least one of deionized water, anhydrous ethanol and n-hexane; Preferably, the slurry is mixed by ball milling, the ball milling atmosphere is at least one of air, nitrogen, argon, carbon dioxide, carbon monoxide, hydrogen, and methane, the diameter of the grinding balls for ball milling is 0.1-100 cm, the mass ratio of the grinding balls to the silicon-based material / graphene slurry is 1:(0.001-1000), the ball milling time is 0.01-100 h, and the ball milling speed is 10-10000 rpm; Preferably, the solid content of the slurry is 0.1-90%.

6. The preparation method according to claim 1, characterized in that: The drying is freeze drying, the freezing temperature is -200 to -5°C, the freezing time is 0.1 to 300 hours, the drying temperature is -100 to 200°C, the drying time is 0.5 to 200 hours, and the vacuum degree is 0.01 to 10 5 Pa, drying times are 1 to 20 times.

7. The preparation method according to claim 1, characterized in that: The flash Joule heat has a temperature of 100-4000K, a voltage of 0.001-10kV, a current of 0.1-100A, a heating rate of 10-3000K / s, a holding time of 0.01-5000s, a cooling rate of 10-2000K / s, and a vacuum degree of 0.001-10 5 Pa, the atmosphere is at least one of air, argon, nitrogen, oxygen, hydrogen, and carbon dioxide.

8. A silicon-based / silicon carbide / graphene composite material prepared by the preparation method according to any one of claims 1 to 7.

9. The silicon-based / silicon carbide / graphene composite material according to claim 8, characterized in that: The silicon-based material loading in the silicon-based / silicon carbide / graphene composite material is 0.1-95%.

10. Use of the silicon-based / silicon carbide / graphene composite material according to claim 8 or 9 as a negative electrode of a lithium-ion battery.

Citation Information

Cited By

  • Si-coated SiC-coated EG ternary composite material as well as preparation method and application thereof

    CN121439760A